HIV-1 glycan density drives the persistence of the mannose patch within an infected individual - Coss, K; Vasiljevic, S; Pritchard, L; Krumm, S; Glaze, M; Madzorera, S; Moore, P; Crispin, M; Doores, K (American Society for Microbiology, 2016)
The HIV envelope (Env) is extensively modified with host-derived N-linked glycans. The high density of glycosylation on the viral spike limits enzymatic processing resulting in numerous under-processed oligomannose-type glycans. This extensive glycosylation not only shields conserved regions of the protein from the immune system but also act as targets for HIV broadly neutralizing antibodies (bnAbs). In response to the host immune system, the HIV glycan shield is constantly evolving through mutations affecting both the positions and frequencies of potential N-linked glycans (PNGSs). Here, using longitudinal Env sequences from a clade C infected individual (CAP256), we measure the impact of the shifting glycan shield during HIV infection on the abundance of oligomannose- type glycans. By analyzing the intrinsic mannose patch from a panel of recombinant CAP256 gp120s displaying high protein sequence variability and changes in PNGS frequency and positioning, we show that the intrinsic mannose-patch persists throughout the course of HIV infection and correlates with the number of PNGSs. This effect of glycan density on processing state was also supported by the analysis of a cross-clade panel of recombinant gp120 glycoproteins. Together, these observations underscore the importance of glycan clustering for the generation of carbohydrate epitopes for HIV bnAbs. The persistence of the intrinsic mannose patch over the course of HIV infection further highlights this epitope as an important target for HIV vaccine strategies.